The relationship between myocardial perfusion scanning results, C-reactive protein to albumin ratio, systemic inflammatory response index and coronary angiographic findings - Yasin Yüksel; Cennet Yıldız (National Scientific Medical Center, 2022)
Aim: We aimed to investigate whether C-reactive protein to albumin ratio (CAR) and systemic inflammatory response index (SIRI) have an additional value in interpretation of myocardial perfusion scanning (MPS) results. Background: MPS have high sensitivity but relatively low specificity in diagnosis of coronary artery disease (CAD). Material and methods: 449 patients who had MPS before coronary angiography were included.  Patients with and without CAD constituted study (n=227) and control (n=222) groups, respectively. Results: Sensitivity and specificity of MPS in detecting CAD were found to be as 97.8% and 62.2%, respectively.  CAR value of 1.22 and SIRI value of 1.45 predicted CAD with a sensitivity of 61.2% and 59% and specificity of 77% and 80.2%, respectively. Only 10.4 % of the CAD negative patients had positive MPS and positive CAR values, whereas 0.9% of the CAD positive patients had negative MPS and negative CAR values.  27.5% of CAD negative patients had positive MPS and negative CAR values. Likewise, having a negative MPS with negative SIRI value identified 50% of the patients who had normal coronary arteries. Positive MPS with positive SIRI value correctly identified 58.1% of patients who had CAD. Conclusion: evaluation of CAR and SIRI might be beneficial in interpretation of MPS.